2013
DOI: 10.1038/ki.2012.441
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics: regulatory mechanisms and emerging role in renal pathophysiology

Abstract: Mitochondria are a class of dynamic organelles that constantly undergo fission and fusion. Mitochondrial dynamics is governed by a complex molecular machinery and finely tuned by regulatory proteins. During cell injury or stress, the dynamics is shifted to fission, resulting in mitochondrial fragmentation, which contributes to mitochondrial damage and consequent cell injury and death. Emerging evidence has suggested a role of mitochondrial fragmentation in the pathogenesis of renal diseases including acute kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
313
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(324 citation statements)
references
References 147 publications
11
313
0
Order By: Relevance
“…[24][25][26][27] Mitochondrial dysfunction can weaken a cell's capacity to respond to a range of metabolic processes, including additional oxidative stress and fatty acid overload, and can contribute to progressive disease. 3,28 A transgenic mouse model has shown that mitochondrial dysfunction in podocytes induced by TGF-b signaling preceded the manifestation of segmental glomerulosclerosis. 29 In addition, diabetic mouse models and in vitro studies have demonstrated that hyperglycemia induced mitochondrial fragmentation in podocytes, endothelial cells, and renal tubular cells.…”
Section: Main Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…[24][25][26][27] Mitochondrial dysfunction can weaken a cell's capacity to respond to a range of metabolic processes, including additional oxidative stress and fatty acid overload, and can contribute to progressive disease. 3,28 A transgenic mouse model has shown that mitochondrial dysfunction in podocytes induced by TGF-b signaling preceded the manifestation of segmental glomerulosclerosis. 29 In addition, diabetic mouse models and in vitro studies have demonstrated that hyperglycemia induced mitochondrial fragmentation in podocytes, endothelial cells, and renal tubular cells.…”
Section: Main Findingsmentioning
confidence: 99%
“…First, mitochondrial dysfunction in kidney cells has been implicated in the pathogenesis of CKD [3][4][5] and proposed as a therapeutic target for atherosclerotic renovascular disease. 8,17 Mitochondrial dysfunction can be a consequence of oxidative stress.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disruption of either fission or fusion can contribute to mitochondrial dysfunction. 40 Hence, there has been considerable interest in targeting mitochondria to improve or maintain mitochondrial stability and prevent tissue damage. 41 Our findings on mitochondrial respiratory function and ultrastructure in S1P1-overexpressing TKPTS cells suggest that S1P1 could be a suitable target for maintaining mitochondrial integrity in kidney tubule cells.…”
Section: Mitochondrial Pcr Array Reveals Change In Expression Of Genementioning
confidence: 99%